Local places and cultural distinction: The booktown model. (August 2018) - Driscoll, Beth
The international development of booktowns during the late 20th and early 21st centuries has facilitated the accumulation of cultural capital for small towns by mobilizing the prestige of books as cultural objects. This article investigates the booktown phenomenon through a case study of Clunes, a village in regional Australia that has been designated as a booktown since 2007. The Bourdieusian approach of the article investigates cultural intermediaries and audiences at booktown, drawing on interviews and analysis of annual reports. These suggest two key findings. First, while Clunes Booktown participates in a range of regional, national and international networks, these work to focus attention strongly at the local level of the village. Second, the booktown designation relies upon and sometimes shores up the association of books with cultural distinction. Findings also suggest that the peripheral setting of Clunes may offset some of the exclusivity of book culture, as the attractions of the village and its non-book-related activities enable different forms of participation and potentially open up literary culture to a broader public.